Pemikiran Pendidikan Islam Azyumardi dan Kontribusinya Bagi Pendidikan Islam di Indonesia - Zulfia Z, Namira; Joutulis, Murid; Muzaki, Ahmad (International Journal Labs, 2025)
This research discusses Azyumardi Azra's thoughts in the field of Islamic education and his important contribution in enriching and updating the Islamic education system in Indonesia. As a forward-looking Muslim intellectual, Azyumardi is known for his ideas on the integration of Islamic science and general knowledge, as well as his views in favor of a moderate Islamic approach to education. This study uses a literature study approach by examining Azyumardi's works and examining their contribution to the policy and implementation of Islamic higher education in Indonesia. The results of the analysis show that Azyumardi's thinking plays a major role in encouraging institutional reform of Islamic education, especially in the process of transformation from IAIN to UIN, as well as in strengthening moderate and inclusive Islamic values in the academic environment. His ideas also play a role in building an education system that is more open, adaptive, and responsive to the challenges of modern times. the importance of curriculum reform, improving the quality of human resources, and strengthening moderate religious literacy as a concrete form of Azyumardi's thought. Efforts to preserve and develop these ideas are indispensable in today's Islamic education so that future generations of Muslims will be able to face global challenges without losing their religious identity. Therefore, Azyumardi Azra's intellectual contribution is the main foundation in the process of modernizing Islamic education in the country and should continue to be studied in contemporary academic discourse.